2014
DOI: 10.1182/blood.v124.21.494.494
|View full text |Cite
|
Sign up to set email alerts
|

The Tumor Microenvironment in Mantle Cell Lymphoma (MCL): Novel Targets to Overcome Chemo-Resistance in MCL

Abstract: Mantle Cell Lymphoma (MCL) is a relatively uncommon, aggressive form of B-cell non-Hodgkin’s lymphoma (NHL), defining approximately 5-8% of adult NHL in the United States. Although individual survival times have increased in recent years, prognosis remains among the poorest of NHL, with a median survival of 5 to 7 years. Despite an initial response to chemotherapy, MCL cells remain residually in the marrow and digestive tract, making MCL prone to recur leading to short survival prognosis. The characteristic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Several studies have highlighted the central role of the microenvironment in the expansion and chemoresistance of B-cell lymphomas, including MCL (11)(12)(13)(14)(15)(16)42). The few works that have examined the role of macrophages in MCL suggested a protumoral function (23,24), especially through the induction of a VEGF-dependent lymphangiogenesis (24). However little was known about the molecular interplay between MCL cells and associated monocytes/macrophages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have highlighted the central role of the microenvironment in the expansion and chemoresistance of B-cell lymphomas, including MCL (11)(12)(13)(14)(15)(16)42). The few works that have examined the role of macrophages in MCL suggested a protumoral function (23,24), especially through the induction of a VEGF-dependent lymphangiogenesis (24). However little was known about the molecular interplay between MCL cells and associated monocytes/macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Among accessory cells, tumor-associated macrophages are known to play a critical role in solid tumor progression (17,18) and have also been described in several B-cell malignancies (19)(20)(21)(22). Previous studies suggested the presence of macrophages in MCL lymph nodes (23,24) but their phenotype and the molecular dialogue that occurs between MCL cells and associated macrophages remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Mantle cell lymphoma (MCL), an aggressive subtype of B-cell lymphoma, has a complex tumor-immune microenvironment (TIME) that impacts tumor growth, progression and treatment outcome [1][2][3]. The composition of the TIME is highly variable across patients and includes various immune cell subtypes, such as T cells, macrophages, neutrophils and dendritic cells, but also soluble factors [4].…”
mentioning
confidence: 99%